2013
DOI: 10.1371/journal.pone.0051837
|View full text |Cite
|
Sign up to set email alerts
|

DREAM Mediated Regulation of GCM1 in the Human Placental Trophoblast

Abstract: The trophoblast transcription factor glial cell missing-1 (GCM1) regulates differentiation of placental cytotrophoblasts into the syncytiotrophoblast layer in contact with maternal blood. Reduced placental expression of GCM1 and abnormal syncytiotrophoblast structure are features of hypertensive disorder of pregnancy – preeclampsia. In-silico techniques identified the calcium-regulated transcriptional repressor – DREAM (Downstream Regulatory Element Antagonist Modulator) - as a candidate for GCM1 gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Although a key assumption in studying mRNA expression is that it is informative in the prediction of protein expression, an important limitation of our study was that only DREAM mRNA levels were measured. Nevertheless, some authors have demonstrated that DREAM mRNA and protein levels were correlated in different tissues in human and rats [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a key assumption in studying mRNA expression is that it is informative in the prediction of protein expression, an important limitation of our study was that only DREAM mRNA levels were measured. Nevertheless, some authors have demonstrated that DREAM mRNA and protein levels were correlated in different tissues in human and rats [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no such association between the maternal genotype and the risk of preeclampsia, however. This was presumably related to the selective expression of GCM1 in the placenta being where the modulation of risk emerges [56] and the fact that most of the placenta is of fetal origin [6]. The same group who found the fetal GCM1 association had previously found an association between the risk of maternal preeclampsia and a fetal SNP in the transforming growth factor (TGF)-b3 (TGFB3) gene in the same group of women [57].…”
Section: Human Studiesmentioning
confidence: 99%
“…SUMOylation has been implicated in the alteration of placental transcription factors regulating trophoblast differentiation including glial cell missing-1 (GCM1) (Chou et al 2007), downstream regulatory element antagonist modulator (DREAM; also referred to as KChIP-3 or calsenilin) (Palczewska et al 2011), p53 (Chiu et al 2008) and hypoxia inducible factor-1α (HIF-1α) (Bhattacharjee et al 2016) by affecting protein stability, activity and intracellular localization. These transcription factors are of particular interest as they have also been shown to be involved in pre-eclampsia disease progression (Chen et al 2004;Baczyk et al 2013b;Sharp et al 2014). Furthermore, we have recently demonstrated that pre-eclamptic placentas exhibit hyperSUMOylation (Baczyk et al 2013a(Baczyk et al , 2017, further suggesting that the dynamic regulation of SUMOs is critically linked to placental function.…”
Section: Introductionmentioning
confidence: 99%